Integrated management of migration, employment, fiscal policy and public debt - Rutkauskas, Aleksandras Vytautas (Business, Management and Economics Engineering, 2013)
The main idea of the paper states that national migration indicators are closely related with employment opportunities in that country. In addition, the management quality of migration and employment processes is an indicator of the national socio-economic policy competency, while management of these processes is the main purpose of intelligent adjustment of the national fiscal policy and government debt management. The author of the paper selected the formation of the system of quantitative indicators as the main objective of the paper. The system should allow employing government debt possibilities for the selection of proper fiscal policy in order to prevent the transformation of unemployment into the key reason of uncontrolled national inflation. This would be done by revealing the possibilities of fiscal policy to impact on the level and structure of unemployment. Recent globalisation processes and integration possibilities bring a lot of uncertainty to predetermined viability of theoretical assumptions as well as the adequacy of the applied quantitative methods. The paper uses the possibilities of stochastic optimisation and stochastically informed expertise pursuing the possibilities of integrated management of employment, migration processes, fiscal policy and government debt provisions.